تأثیر استراتیجیة جیجسو التعاونیة في تعلم مھارة استقبال الإرسال بالكرة الطائرة - شلير حسين عبد الكريم (الرياضة المعاصرة, 2015)
The research aims to identify the impact of Jigsaw cooperative strategy in learning the skill transmission volleyball reception, the detection of a better group to learn and determined the research problem to find educational alternatives through the use of modern methods of teaching and strategies to achieve the goals in the educational environment of the teaching process. As it has been selected (30) student at random from the seventh row of the main stage (the first average), and the average age (12-14 years) attending Elementary School in the district of Kalar Pennekrd for the academic year (2013-2014 m), was tested in skill transmission reception the plane of the ball, as the sample was divided into two groups, the first trial was used Jigsaw cooperative strategy and the second officer used the traditional practice style (Prince). The results showed significant differences between tribal and dimensional tests and in favor of a posteriori tests to learn the skill and the two groups, but we have significant differences between the experimental and control groups did not appear in the skill test.The researcher recommended an emphasis on the use of both traditional and Jigsaw cooperative method applied strategy (Prince) in student learning skill transmission plane receiving the ball, and suggested the researcher conducting studies in other types of strategies and methods of teaching modern and individual and group games She insists on using command teaching style in teaching upper hand serve skills of volleyball . The researcher also suggests the usage of other kinds of modern strategies and method of teaching for Indi victual.